Knockdown of endothelin receptor B inhibits the progression of triple‐negative breast cancer. Issue 1 (22nd March 2019) - Gu, Xi; Han, Shuai; Cui, Meizi; Xue, Jinqi; Ai, Liping; Sun, Lisha; Zhu, Xudong; Wang, Yulun; Liu, Caigang
Abstract: Endothelin receptor B (EDNRB) is one of the receptors in the endothelin axis and its upregulated expression is associated with tumorigenesis and metastasis of several types of solid tumors. However, the expression profile of EDNRB in breast cancer and its role in the progression of breast cancer are unclear. Here, we show that EDNRB expression is higher in metastatic tumors than in primary breast cancer, and is associated significantly with lymph node metastasis and poor survival in Chinese patients with breast cancer. EDNRB expression was particularly upregulated in triple‐negative breast cancer (TNBC) cells. Moreover, EDNRB silencing by a specific shRNA significantly attenuated the proliferation, migration, and invasiveness of MDA‐MB‐231 and BT549 cells and increased their apoptosis, as well as retarded the growth of implanted tumors in mice. Tandem mass spectrometry analysis indicated that 248 proteins were differentially expressed in EDNRB ‐silenced cells and their cellular organelles, and these proteins participate in many processes. EDNRB silencing decreased protein kinase B and extracellular regulated protein kinase phosphorylation and promoted the mesenchymal‐to‐epithelial transition process in MDA‐MB‐231 cells. Therefore, our findings provide strong evidence for the first time that knockdown of EDNRB expression inhibits the progression of TNBC and that EDNRB can serve as a prognostic biomarker and therapeutic target for the treatment of TNBC. Abstract : This article demonstrates that endothelin receptor B (EDNRB) is expressed in breast cancer and plays a role in its progression. EDNRB expression is associated significantly with lymph node metastasis and poor survival in breast cancer patients, and is particularly upregulated in triple‐negative breast cancer cells. Silencing of EDNRB in breast cancer cells significantly inhibited their proliferation, migration, and invasiveness, and increased their apoptosis.